Combining Decision Trees And Transformation-Based Learning To Correct Transferred Linguistic Representations - Corston-Oliver, Simon; Gamon, Michael (Association for Machine Translation in the Americas, 2003)
We present a hybrid machine learning approach to correcting features in transferred linguistic representations in machine translation. The hybrid approach combines decision trees and transformation-based learning. Decision trees serve as a filter on the intractably large search space of possible interrelations among features. Transformation-based learning results in a simple set of ordered rules that can be compiled and executed after transfer and before sentence realization in the target language. We measure the reduction in noise in the linguistic representations and the results of human evaluations of end-to-end English-German machine translation.